Proinflammatory Responses of Heme in Alveolar Macrophages: Repercussion in Lung Hemorrhagic Episodes - Rafael L. Simões; Maria Augusta Arruda; Cláudio Canetti; Carlos H. Serezani; Iolanda M. Fierro; Christina Barja-Fidalgo (Mediators of Inflammation)
Clinical and experimental observations have supported the notion that free heme released during hemorrhagic and hemolytic episodes may have a major role in lung inflammation. With alveolar macrophages (AM) being the main line of defense in lung environments, the influence of free heme on AM activity and function was investigated. We observed that heme in a concentration range found during hemolytic episodes (3–30 μM) elicits AM to present a proinflammatory profile, stimulating reactive oxygen species (ROS) and nitric oxide (NO) generation and inducing IL-1β, IL-6, and IL-10 secretion. ROS production is NADPH oxidase-dependent, being inhibited by DPI and apocynin, and involves p47 subunit phosphorylation. Furthermore, heme induces NF-κB nuclear translocation, iNOS, and also HO-1 expression. Moreover, AM stimulated with free heme show enhanced phagocytic and bactericidal activities. Taken together, the data support a dual role for heme in the inflammatory response associated with lung hemorrhage, acting as a proinflammatory molecule that can either act as both an adjuvant of the innate immunity and as an amplifier of the inflammatory response, leading tissue injury. The understanding of heme effects on pulmonary inflammatory processes can lead to the development of new strategies to ameliorate tissue damage associated with hemorrhagic episodes.